2018
DOI: 10.1177/0022146517749848
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Health Consequences of Adverse Labor Market Conditions at Time of Leaving Education: Evidence from West German Panel Data

Abstract: Using longitudinal survey data from the Socio-Economic Panel Study ( N = 3,003 respondents with 22,165 individual-year observations) and exploiting temporal and regional variation in state-level unemployment rates in West Germany, we explore differences in trajectories of individuals' self-rated health over a period of up to 23 years after leaving education under different regional labor market conditions. We find evidence for immediate positive effects of contextual unemployment when leaving education on indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…The explanation for this may be the higher mortality and non-responses rates among the participants with the poorest self-rated health (Andersen et al, 2007) and the compensatory mechanisms within individuals' social capital networks to face adverse events such as unemployment (Piumatti, 2016;Piumatti et al, 2018b;Saltkjel et al, 2017). Previous studies have in fact reported that while at the overall country level we may observe stable or positive trends in SRH during time of crisis even in the most affected regions, contrasted trends in health outcomes may still take place across specific portions of the population (Clause-Verdreau et al, 2018;Lersch et al, 2018;Saltkjel et al, 2017).…”
Section: Resultsmentioning
confidence: 95%
“…The explanation for this may be the higher mortality and non-responses rates among the participants with the poorest self-rated health (Andersen et al, 2007) and the compensatory mechanisms within individuals' social capital networks to face adverse events such as unemployment (Piumatti, 2016;Piumatti et al, 2018b;Saltkjel et al, 2017). Previous studies have in fact reported that while at the overall country level we may observe stable or positive trends in SRH during time of crisis even in the most affected regions, contrasted trends in health outcomes may still take place across specific portions of the population (Clause-Verdreau et al, 2018;Lersch et al, 2018;Saltkjel et al, 2017).…”
Section: Resultsmentioning
confidence: 95%
“…Most arguments suggest that the economy played a crucial role (Case and Deaton 2017) because recent labor market shifts decreased the value and availability of the blue-collar jobs that once supported middle-class lifestyles among men without a college degree. Indeed, work is an important contributor to mental and physical health through both the ability to find good, steady work (Lersch, Jacob, and Hank 2018) and the types of benefits, hours, pay, and responsibilities one has within a job (De Moortel et al 2017;Mirowsky and Ross 2007;Schneider and Harknett 2019). Labor market shifts over the past few decades increased inequality (Dwyer 2013;Mouw and Kalleberg 2010), job precarity (Kalleberg 2009), and physical and mental health problems, which may feed into feelings of hopelessness and despair (Goldman, Glei, and Weinstein 2018) that increase vulnerability to suicide and drug poisoning deaths (Durkheim [1897(Durkheim [ ] 1951.…”
mentioning
confidence: 99%